Structure and tissue-specific expression of the human metallothionein IB gene. - Heguy, A (1986)
The human metallothionein (MT) IB gene (hMT-IB) is located in a region of human DNA containing at least four tandemly arranged MT genes. As deduced from its sequence, hMT-IB is likely to encode a functional protein. However, the predicted amino acid sequence differed from the hMT-I amino acid sequence in four positions. Most remarkable was the presence of an additional cysteine. Like other MT genes, hMT-IB has at least two copies of the metal-responsive element upstream from the transcription initiation site. These elements probably are responsible for the metal responsiveness of the hMT-IB promoter, leading to inducible expression of fused heterologous genes. Unlike the hMT-IIA and hMT-IA genes described previously, which are expressed in many different cell types, a high level of expression of the endogenous hMT-IB gene could be detected only in human hepatoma and renal carcinoma cell lines. Therefore, this is the first MT gene described which exhibits tissue specificity of expression. This specificity is controlled by a cis-acting mechanism involving methylation, since incubation of nonexpressing cells with an inhibitor of DNA methylation led to activation of the hMT-IB gene. In support of this notion, we found that the 5' flanking region of the hMT-IB gene was highly methylated in HeLa cells, a nonexpressing cell type, but it was not methylated in a hepatoma (expressing) cell line.